Intraoperative Use of CBCT for Identification and Localization of Calcified Canals: A Clinical Technique - Spyros Floratos; Maria-Elpida Miltiadous (Case Reports in Dentistry)
Localization of calcified canals has always been a challenge in the field of endodontics. The following report of three cases describes a technique for the identification and negotiation of obliterated canals by use of cone beam computed tomography (CBCT) intraoperatively. Canal orifices could not be found clinically in all three cases. Gutta-percha points were placed and compacted at the position where the canal orifices were estimated to be. Intraoperative CBCT was taken, and the distance between the gutta-percha points and the canal orifices was calculated at all planes of space in the first two cases. In the third case, only one canal orifice could be identified due to obliteration of the other canals.